Kajian Mekanisme Molekuler Golongan Obat Antihipertensi Dalam Menghambat Angiotensin-Converting Enzyme (ACE) - Jekmal Malau; Munir Alinu Mulki; Nur Komala Fitri; Najla Yusiana Wahyudi; Priscinya Christiana Debora; Mulidini Mulidini; Nolla Olipia Elva Megrian; Nissa Khalida Hanum (Jurnal Ilmiah Wahana Pendidikan, 2023)
Hypertension or increased blood pressure is a chronic disease that requires long treatment, even for life. Patients with hypertension must control their blood pressure to avoid complications. In the body, there are components of the renin-angiotensin system, namely the angiotensin-converting enzyme (ACE) which can indirectly increase blood pressure, so the treatment is to inhibit ACE. In this article, the method used is by literature study of several accredited journals that has published from 2012 to 2022. ACE inhibitor class drugs are often used for the treatment of hypertension because they have a mechanism of inhibiting the conversion enzyme peptidyl dipeptidase, so that angiotensin I is not hydrolyzed to angiotensin II and can be contributed for dilating blood vessels as well so that it effectively lowers blood.